Morfofuncionalidade de plântulas de espécies lenhosas de uma área de restinga - ALVES, Maria Claudjane Jerônimo Leite (2011)
After germination, the seedling stage is the critical moment for the establishment of plant species, both in their natural environment and in the greenhouse. Work on morfofunção seedling can provide essential information to clarify issues related to ecological succession, and contribute in the work of inventory, conservation and regeneration of natural ecosystems, since they contribute to understanding the roles of morphological structures in the processes of development and establishment plants. This study aimed to characterize the seedling morfofunção 28 woody species from a tropical coastal vegetation (Restinga forest) of relating them to the status of succession and the regeneration of the area. The study was conducted in a sandy plain forest located on the southern coast of Pernambuco, Brazil. Monthly collections, from July/2009 to July/2010, were performed to obtain seeds from at least three individuals, with a diameter at ground height (DAS) 10 cm. In the laboratory the fruits were pulped and the seeds germinated. As a result the species were subdivided into four categories morphofunctional, 13 of type-phanero-epigeal foliaceous (PEF), three-phanero epigealreserve (PER), three-phanero-hypogean (PHR) and crypto-nine hypogeal-reserve (CHR). Pearson correlation analysis and chi-square tests were significant between the seedling morfofunção and studied the ecological characteristics (level of succession, seed weight, dispersal syndrome and shade tolerance). Among the pioneer species, with cotyledons PEF, most had small seeds and light, growing preferably in sunny locations. Moreover successional species with CHR cotyledon presented largely with larger seeds and high amount of reserves,growing and establishing themselves in shady sites. There was a predominance of fruit with seed dispersal by animals between PEF and CHR seedlings, suggesting that these morphofunctional types, in particular, provide advantages for survival and growth of individuals who own them. In Maracaípe was observed that the functional morphology of seedlings appears to be related to successional stage area. Thus, we conclude that, at least in the initial stage, the morphology of seedlings can be used as a measure of successional level, contributing to ecological and taxonomic studies.